Mechanical behavior of fdm 3d printed coconut wood-filled pla - Jeevendran, Kananathan (2023)
Fused Deposition Modeling (FDM) is a crucial additive manufacturing (AM) method, and it is an inexpensive 3D printing process for making thermoplastic and composite materials. The FDM technology has made significant contributions to the manufacturing industry because of its capacity to create complicated parts while also providing exact dimensions. Wood particles are widely used in the biomedical sector. On the other hand, little is known about the mechanical characteristics of pure wood. Coconut wood has a long history of being valued for its environmentally beneficial, biodegradable, thermal, and corrosion-resistant properties. Consequently, this study's goal is to characterize the physical and chemical properties of Polylactic acid (PLA), Coconut wood (Ct.W), and customized PLA/ Ct.W composite. The mechanical properties of PLA and PLA/Ct.W specimens were next investigated in accordance with ASTM standards. For example, tensile testing following ASTM D638 Type 1, compression testing following ASTM D695, bending testing following ASTM D790, and lastly, impact testing following ASTM D256. Using the FDM process on PLA made from coconut wood, testing specimens were created with various infill percentages (25%, 50%, and 75%) and infill patterns (rectilinear, honeycomb, grid, concentric, and octagram spiral). Next, the mechanical properties of PLA and PLA/Ct.W was determined after tensile, bending, compression, and impact testing. The response surface methodology (RSM) is then used to further examine the experiment's data in order to pinpoint the optimal parameter that has the greatest impact on the mechanical properties. RSM was also utilised to construct mathematical models of the mechanical properties that may be used to forecast desired mechanical properties with different infill percentages and infill patterns. The response surface methodology (RSM) is then used to examine the experiment's data further to pinpoint the optimal parameter that impacts the mechanical properties most. The morphology of coconut powder displays spherical microparticles, and the size of the coconut powder ranges between 1.78 μm. to 3.88 μm. FTIR group shows that the coconut wood powder had a carboxyl band stretching at 1240 and 1034 cm-1 showing an adequate interlayer bonding between the PLA and Ct.W. According to the experimental findings, a concentric infill pattern and a 75% infill percentage produced the best results in both bending and tensile tests. Grid infill patterns with 75% infill rates provide the best compression properties for testing. Lastly, for the impact testing, the honeycomb infill pattern and 75% infill percentage of specimen has the highest impact properties. Overall, the octagram spiral infill pattern shows the weakest properties among all the infill patterns. Also, using the RSM, the regression equations were created to achieve the maximum properties using the PLA/Ct.W composite. As a recommendation, using bonding agents to increase the bonding of the PLA and Coconut wood materials and reduce the particle size of the coconut wood will help enhance the quality of the product. To determine the precise impact of printing parameters on the mechanical property of printed specimens and to improve the strength of PLA/Ct.W based FDM specimens and products in the future, parameters like layer thickness, air gap, and raster angle can also be changed along with infill percentage and infill pattern. Also, the present research contributes Sustainable development goals (SDGs) number-8 Decent work and economic growth and number-12 Responsible consumption and production.